Metode Kaizen dan 5 Why Analysis untuk Memperbaiki Efisiensi, Kualitas dan Cost Produksi Dibagian Painting: Studi Kasus PT. XYZ - Asidiq, Annaas Nurhuda; Santoso, Roland Amirullah; Firdaus, Reiffan Wahyu; Maryadi, Adithya; Kurniawan, Rachman Catur (DPPM UNIVERSITAS PELITA BANGSA, 2023)
This study investigated the effectiveness of Kaizen and 5 Why Analysis for improving production efficiency, quality, and cost in a painting department at PT. XYZ. The research employed a case study approach, focusing on the issue of dust defects on painted products. 5 Why Analysis identified several root causes, including airborne dust, unclean surfaces, and inadequate pre-painting cleaning. The Quality Control Circle (QCC) team implemented solutions such as installing dust collectors, implementing pre-surface cleaning, blowing units before surface treatment, covering buffer mouths, and adding automated tagging. These interventions led to a significant reduction in dust defects, subsequently enhancing product quality and production efficiency. Additionally, production costs decreased due to reduced rework and fewer defective products.